ESTRATÉGIAS PARA A MELHORIA DA ATENÇÃO À SAÚDE DE HIPERTENSOS ATENDIDOS NA ATENÇÃO PRIMÁRIA À SAÚDE - SANTOS, Kelly Emmanuelle de Sousa Araújo (2024)
Introduction: Systemic Arterial Hypertension is a major challenge for Brazilian and global public health, due to its high prevalence, and mainly due to the high rate of physical disabilities and deaths resulting from its complications. It has a significant prevalence in Primary Health Care and risk factors such as sedentary lifestyle, smoking, alcoholism, inadequate diet, obesity, difficulty in accessing health services and poor adherence to treatment are frequently identified during care. Objective: To develop strategies to increase adherence to both pharmacological and non-pharmacological treatment of Systemic Arterial Hypertension, and health care for hypertensive patients treated in Primary Care in the city of Caxias-MA. Methodology: This is an exploratory, descriptive, cross-sectional research with a quantitative and qualitative approach, carried out in the territories covered by Primary Care. The variables of interest were recorded through a semi-structured questionnaire with direct questions and a dialogued interview. Results: The study sample consisted of patients aged 24 to 96 years, with a predominance of individuals aged 50 to 79 years (43%), women (73%), married (59%), selfdeclared brown skin color (64.3%), predominantly illiterate (39.3%) and family income between 1 and 2 minimum wages (67.7%), who presented the following difficulties in adhering to treatment: lack of information about the disease, difficulties in adopting lifestyle changes and incorrect use of medications. In addition to lack of knowledge about the HIPERDIA program. Final considerations: Most users are unaware of the severity of the disease, making it difficult to adhere to treatment for high blood pressure. Health education enables changes and generates autonomy for those involved, in addition to essential inclusion in the transformation of factors that directly impact the lives of patients, especially in the most vulnerable groups. The multidisciplinary team is an important tool for promoting health by providing knowledge to hypertensive patients, making them committed to improving their lifestyle habits and encouraging self-care and seeking autonomy.